Mortality rate of lip, oral cavity and pharynx malignant tumors in Serbia within a period 1991–2009 - Ilić, Milena; Radević, Svetlana; Stefanović, Vladimir; Ćirković, Tatjana; Zurovac, Tamara; Savić, Borivoje; Kovačević, Vladan (Vojnosanitetski pregled, 2013)
Background/Aim. Lip, oral cavity and pharynx malignant tumors account for 3.7% of all cancer deaths worldwide, with significant geographic variations in frequency and distribution. The aim of this descriptive epidemiologic study was to analyze the mortality rate of lip, oral cavity and pharynx malignant tumors in Serbia proper within a period 1991–2009. Methods. Mortality rates standardized directly using the world population as the standard were used in data analysis. Linear trend and regression analyses were used to analyze rate trends in mortality. Results. The Serbian population demonstrated an increase in the mortality of lip, oral cavity and pharynx malignant tumors (y = 3.32 + 0.03×; p = 0.002; average annual percent change = + 0.8). The male population showed a significant increase in mortality trend (y = 5.90 + 0.03×; p = 0.020; % change = + 0.9), while the female population did not show a significant increase in mortality. The male/female cancer mortality ratio was 5.5:1. Mortality rates for lip, oral cavity and pharynx cancer increased with age in both genders, with rates being the highest in the population aged 85 and older. Increasing trends of lip, oral cavity and pharynx cancer mortality were observed in males aged 50–54; the average annual percent change was + 7.4 % (95% CI, 6.2–9.0). The population of both genders aged 55–59 demonstrated an increase in lip, oral cavity and pharynx cancer mortality, the increase being + 1.8% (95% CI, 1.4–2.2) in men and + 34.3% (95% CI, 28.4–40.2) in women. Conclusion. The increasing trend in lip, oral cavity and pharynx cancer mortality points to the necessity to investigate etiology and improve primary and secondary prevention measures.